Usulan perbaikan kualitas produk benang combed dengan metode statistik peta kendali x dan r - Yoga Nur Ashasry; Kusnadi Kusnadi; Asep Erik Nugraha; Hamdani Hamdani (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2021)
PT. ILT is a company engaged in the production of spinning yarn. There are various types of yarn produced by PT. One of ILT's yarns is Combed 40s (CM 40/1). The purpose of this study was to evaluate the product quality of combed 40s yarn, so that improvements can be made. The data used in this study is in the form of direct testing results in the company. Data processing is carried out using control charts X and R to determine whether the production results are in accordance with the standard or not. Measurements were made on 4 criteria, namely thread number (Ne), twist (TPI), strength, and unevenness. The results obtained are known that all measurement criteria are within the control limits on the X and R control charts. Meanwhile, the comparative analysis of measurement results with company standards is known that existing standards are still too loose. This causes the quality of the resulting product is still not optimal. Therefore, it is necessary to revise the standards for each criterion. It aims to improve the quality of the products produced by increasing awareness of employee performance.